Design, Synthesis, and Evaluation of Novel Antidiabetic Agents (Metformin Analogues) with Improved Efficacy and Reduced Risk of Hypoglycemia for Long-Term Management of Type 2 Diabetes - Vinod Wankhede, Sujata; Kumar Gupta, Vinay; Gahlot, Vinod; Arun Kumawat, Jaymala; Patel, Ashish; Sharma, Deepanshu; Kumar, Anil; P. Patel, Kinjal; Sri Venkatesh, Uriti (Journal of Neonatal Surgery, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disorder characterized by insulin resistance and impaired glucose regulation. Metformin, the first-line therapy, has limitations such as gastrointestinal intolerance and risk of lactic acidosis, necessitating the development of novel analogues with improved efficacy and safety. This study designed, synthesized, and evaluated five metformin analogues: DMAA, PBG, BMB, TZD-Met, and SFBG, aiming to enhance glucose uptake, insulin sensitivity, and mitochondrial function while reducing adverse effects. Methods: A series of metformin analogues were synthesized via structural modifications to the biguanide backbone. Chemical characterization was performed using FTIR, NMR (¹H and ¹³C), MS, and X-ray crystallography. In vitro glucose uptake assays were conducted in L6 myotubes and HepG2 cells, followed by AMPK activation (Western blot) and GLUT4 translocation (Immunocytochemistry) studies. In vivo efficacy was assessed in high-fat diet (HFD)-induced Type 2 diabetic mice, with treatment groups including vehicle control, metformin, and the five analogues. Parameters evaluated included Fasting Blood Glucose (FBG), Oral Glucose Tolerance Test (OGTT), HbA1c, HOMA-IR, and organ toxicity markers. Results: Chemical synthesis confirmed successful modifications, as validated by spectral analysis. Glucose uptake increased significantly (p < 0.05) in all analogues compared to metformin, with SFBG and TZD-Met demonstrating the highest enhancement. AMPK phosphorylation (p-AMPK/AMPK ratio) was significantly higher in analogue-treated cells compared to metformin. GLUT4 translocation to the plasma membrane was increased in all analogues, correlating with improved glucose uptake. In vivo studies showed a significant reduction in FBG levels over 12 weeks, with TZD-Met and SFBG outperforming metformin by 15–20%. HOMA-IR index indicated enhanced insulin sensitivity in the analogue-treated groups, particularly BMB and DMAA. Toxicity assessment showed reduced gastrointestinal side effects and lower risk of lactic acidosis compared to metformin. Conclusion: The novel metformin analogues exhibited superior glycemic control, increased AMPK activation, and enhanced insulin sensitivity with an improved safety profile compared to metformin. These findings suggest that structural modifications to biguanides may offer next-generation antidiabetic therapies with reduced side effects. Future studies should focus on pharmacokinetics, clinical translation, and long-term metabolic outcomes to establish their therapeutic potential in T2DM management.